The Association Between Comorbid Hypertension and the Severity of COVID-19 at National Emergency Hospital Wisma Atlit Kemayoran Jakarta (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
The severity of COVID-19 is influenced by many factors, one of which is comorbid hypertension. The National Emergency Hospital Wisma Atlit Kemayoran is a special hospital and the only hospital that treats patients from severe to asymptomatic. This study aims to look at the association between comorbid hypertension and the severity of COVID-19. The design of this study was a case control conducted from October to November 2022. The data used was the secondary data from the medical records of patients at National Emergency Hospital Wisma Atlit Kemayoran in 2021. The case group totaled 288 research subjects who experienced COVID-19 with moderate and severe symptoms, while the control group totaled 302 research subjects who experienced COVID-19 with mild and asymptomatic symptoms. The results showed a statistically significant association between hypertension and the severity of COVID-19 with OR 3.40, 95% CI 1.88 to 6.34 and p-value <0.001. There is also a statistically significant association between comorbid hypertension and the severity of COVID-19 with Adjusted OR 3.33, 95% CI 1.79 to 6.13 and p-value <0.001 after being controlled by age, vaccination status, and education level. It is hoped to be an illustration that the management of hypertension is very important in order to prevent the worsening of the condition in COVID-19 patients.